Advances in lipid methodology - Adlof, Richard O. (Oily Press lipid library, 2003)
The fifth volume in the Advances in lipid methodology series is the first with new editor, Richard O. Adlof, but its objectives are still those of the previous editor, William W. Christie: 'To provide readable, up-to-date reviews of rapidly expanding areas of lipid analysis and practical examples which should be of immediate use to lipid analysts'. As in the previous volumes of Advances in lipid methodology, the editor has chosen leading international experts to write individual chapters. Volume 5 contains four chapters on specific methodologies of lipid analysis and three which describe specific applications or standardization of methods. The methodologies are different scanning calorimetry for the study of physical properties of fats and oils; silver ion chromatography; atmospheric-pressure chemical-ionization mass spectrometry (APCI-MS); and supercritical fluid chromatography (SFC). Chapters on specific applications cover the analysis of genetically modified oils and the use of fatty acid profiling in the characterization of metabolic diseases. A further chapter provides an overview of the official standard methods used for fats and oils analysis and gives extensive listings of information on standards organizations.